Is polycystic ovary syndrome a 20th Century phenomenon?. (March 2019) - Rodgers, Raymond J.; Suturina, Larisa; Lizneva, Daria; Davies, Michael J.; Hummitzsch, Katja; Irving-Rodgers, Helen F.; Robertson, Sarah A.
Abstract: Polycystic ovary syndrome (PCOS) affects around 10% of women of reproductive age and is most common in developed countries. The aetiology of PCOS is not completely understood. Current evidence suggests that the syndrome results from a genetic predisposition interacting with developmental events during fetal or perinatal life that together increase susceptibility in some individuals. This implies that environmental factors influence the initiation of PCOS in the fetus or infant, either directly or via the mother. PCOS is often considered to be an ancient disorder but there is no direct proof of this in the medical or historic record. One of the cardinal features, polycystic ovaries, was first described only in the early 1900s, despite reports of many thousands of autopsies recorded earlier. This conundrum could be explained by postulating that polycystic ovaries were rare before the 1900s and have become more common over the last 100 years. The hypothesis that PCOS is a syndrome of the 20th Century would eliminate the need to explain the paradox of why there exists a genetic predisposition to subfertility syndrome.